2016
DOI: 10.15389/agrobiology.2016.4.533eng
|View full text |Cite
|
Sign up to set email alerts
|

SOME NATURAL AND SYNTHETIC COMPOUNDS INHIBITING THE BIOSYNTHESIS OF AFLATOXIN B1 AND MELANIN IN Aspergillus flavus

Abstract: A b s t r a c tThe control of the mycotoxin contamination of agricultural products represents a serious problem of the global food and feed industry. Aflatoxin B1 (AFB1) is one of the most dangerous mycotoxins due to its hepatotoxicity, carcinogenicity, and temperature resistance. Thus, the search for substances able to block its biosynthesis and, therefore, to prevent the toxin accumulation in food and feed is still relevant. This paper is devoted to the study of the ability of some natural and synthesized co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
(16 reference statements)
4
1
0
Order By: Relevance
“…We found that other phosphate-containing compounds inhibited melanization in a similar manner including phosphoserine, phosphoacetic acid, pyrophosphate, and phosphoric acid. This is in line with literature reports that other aminophosphonic acids inhibit fungal eumelanin in the human pathogen Aspergilius flavus [ 118 ]. Incidentally, this class of compounds is patented for use in human cosmetics and is marketed as solutions to inhibit melanogenesis in the skin [ 119 , 120 ].…”
Section: Discussionsupporting
confidence: 93%
“…We found that other phosphate-containing compounds inhibited melanization in a similar manner including phosphoserine, phosphoacetic acid, pyrophosphate, and phosphoric acid. This is in line with literature reports that other aminophosphonic acids inhibit fungal eumelanin in the human pathogen Aspergilius flavus [ 118 ]. Incidentally, this class of compounds is patented for use in human cosmetics and is marketed as solutions to inhibit melanogenesis in the skin [ 119 , 120 ].…”
Section: Discussionsupporting
confidence: 93%
“…An increased AFB1 production was also observed in the case of thymol and 3-HBA. Thus, the effect of these three compounds was similar to that observed earlier for N -hydroxyputrescine and (1-aminoethyl)phosphonic acid [24]. …”
Section: Resultssupporting
confidence: 85%
“…We also revealed several such compounds in our previous studies [14,24]. This effect can be explained by the common initial biosynthetic stages of both metabolites first hypothesized by Brown and Salvo [13].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…We found that other phosphate-containing compounds inhibited melanization in a similar manner including phosphoserine, phosphoacetic acid, pyrophosphate and phosphoric acid. This is in line with literature reports that other aminophosphonic acids inhibit fungal eumelanin in the human pathogen Aspergilius flavus (117). Incidentally, this class of compounds is patented for use in human cosmetics, and are marketed as solutions to inhibit melanogenesis in the skin (118,119).…”
Section: Discussionsupporting
confidence: 81%